Answer:
-12x^2+46x-6
Step-by-step explanation:
combine like tens and subtract then from eachother
The coefficient of y = 3
coefficient = the constant in front of a variable
Constant means that the number will not change.
hope this helps
Without knowing the shape selection you have i cant really say anything. But with a square you wouldnt have any whole numbers, nor would a triangle give you whole number, than again no shape that i can think of would give whole numbers.
A
substitute x = 3h into f(x)
f(3h) = 2(3h)² + 3(3h) - 4 = (2 × 9h²) + 9h - 4 = 18h² + 9h - 4